PENGGUNAAN METODE COMPLETE SENTENCE MELALUI MEDIA GAMBAR SERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SISWA KELAS II SDN 2 PANJER - ISMAYAYANTi, NOVI NIRMALA (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Using Complete Sentence Method through Series Image Media to Improve Essay Writing Skills at Second Grade Student of SDN 2 Panjer. This study aims to describe the steps Complete Sentence learning method through the series image media and improve the skills of essay writing at second grade of elementary school. Research subject is second grade SDN 2 Panjer amount of 27 students. The research was conducted in three cycles, each cycles consisting of planning, implementation, observation, and reflection. Data collection techniques using observation, interviews, and testing. Test the validity of data using triangulation techniques. The results showed that the use of Complete Sentence methods through the series image media can improve essay writing skills second grade of elementary school. Keyword: Complete Sentence, series image media, writing skills Abstrak: Penggunaan Metode Complete Sentence melalui Media Gambar Seri untuk Meningkatkan Keterampilan Menulis Karangan Siswa Kelas II SDN 2 Panjer. Penelitian ini bertujuan mendeskripsikan langkah-langkah pembelajaran menggunakan metode Complete Sentence melalui media gambar seri dan meningkatkan keterampilan menulis karangan siswa kelas II SD. Subjek penelitiannya siswa kelas II SDN 2 Panjer sejumlah 27 siswa. Penelitian dilaksanakan dalam tiga siklus, setiap siklus terdiri atas perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data menggunakan observasi, wawancara, dan tes. Uji validitas data menggunakan teknik triangulasi. Hasilnya menunjukkan bahwa penggunaan metode Complete Sentence melalui media gambar seri dapat meningkatkan keterampilan menulis karangan siswa kelas II SD. Kata Kunci: Complete Sentence, gambar seri, keterampilan menulis